Public archaeology at Baynard-Zion: bringing life back to an antebellum cemetery. Issue 3 (1st September 2020) - Sanger, Matthew C.; Cavanagh, Kimberly; Shamoon-Pour, Michel; Thomas, Richard; Piekut, Linda; Bourcy, Samuel; Seeber, Katherine
ABSTRACT: Heritage tourism is a driving economic force in much of the coastal southeastern United States, including on Hilton Head Island, South Carolina, one of the most popular destinations for vacationers in the country. Working with local community members in developing a diverse and multipronged public archaeology program, we helped facilitate research and develop programing at the Baynard Mausoleum and Zion Chapel of Ease and Cemetery (Baynard-Zion). Built and used during the late eighteenth through mid-nineteenth centuries, Baynard-Zion includes some of the oldest marked graves on the island as well as its oldest standing architecture. Using a constellation of techniques, including geophysical surveys, genetic testing of human remains, and limited excavations, research conducted at Baynard-Zion provides an opportunity to enhance public perception and understanding of pivotal historic events and people on the island while also assisting in development plans that promote heritage tourism.